ANALISA IMPLEMENTASI KONEKSI LABORATORIUM INFORMASI SISTEM (LIS) DENGAN SISTEM INFORMASI RUMAH SAKIT (SIRS) AWAL BROS PEKANBARU - Yusneli, Yusneli; Harnani, Yessi; Ismainar, Hetty; Marlina, Hastuti; Jepisah, Doni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The Laboratory services at Awal Bros Hospital Pekanbaru used Laboratory Information System (LIS) program which connected to the Hospital Information System (HIS). In the implementation of these two systems, there are still obstacles that can hinder service to patients. The purpose of research was to obtain in-depth information on the obstacles faced in implemented the SIRS and LIS system connections at Awal Bros Hospital Pekanbaru. The methode of research used descriptive qualitative with purposive sampling. The Informan of research were 7 peoples. The Collecting data used in-depth interviews, direct observation and document review. The Data analysis used triangulation of methods, sources and data. The results of research showed that there was still a lack of IT human resources, amounted to 5 people, the lack of SIRS and LIS training amounted 20% of 1000 employees, there was no operating standard of HIS, nurses used pdf results to view laboratory examination results instead of EMR, and internet network problems. It can be concluded that the LIS connection with HIS has not gone well. It is necessary to add IT human resources, make operating standard of HIS, and viewer LIS programs from the HIS program.Keywords: HIS, ILS, System Connection